If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(y + 2) = 20 Reorder the terms: -5(2 + y) = 20 (2 * -5 + y * -5) = 20 (-10 + -5y) = 20 Solving -10 + -5y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -5y = 20 + 10 Combine like terms: -10 + 10 = 0 0 + -5y = 20 + 10 -5y = 20 + 10 Combine like terms: 20 + 10 = 30 -5y = 30 Divide each side by '-5'. y = -6 Simplifying y = -6
| 7(4n-1)(2n+11)=0 | | x^2-11x-18=3x+2 | | 7y-7=5y-3 | | 2(2y-1)(y+5)+y(y+5)=0 | | 18(v+1)-2v=4(v+2)-11 | | 7x-4(x-4)+20=25 | | 4z^2(2z+9)(9z-2)=0 | | 3x+12=-4x-9 | | 4x=13x-234 | | 3(x-5)+2x=x+11 | | 2y(y+3)=(4y-2)(y+5)+y(y+5) | | (7m+16)(7-16)=0 | | 2x+3-4x=5x-6 | | 6x+108=9x | | -3x(3x+8)(x-5)=0 | | 9y+5=17 | | 5x+9=-46-6x | | 2x-3=-5(x-4) | | 5(x-3)-(3x-7)= | | 18x^2-27x=3x^3 | | -x^8+(8x)-24=0 | | -3(k-7)(8k+3)=0 | | -2(x+2)=2(-x-1) | | 2cos(t)= | | 8iz^2+16=0 | | 9h-28=35 | | 19(39-2x)=703 | | 21x-10=5(4x+5)-15 | | 3r-4=4r-3 | | 8b-4b-b=55 | | 2n^2(n+6)(n-3)=0 | | 2f+7=8f-23 |